ANALISIS KELAYAKAN USAHA AMPLANG STUDI KASUS UD. OGI PASSOMPE DI DESA JONE, KECAMATAN TANAH GROGOT, KABUPATEN PASER - Rafikah; Fitriyana; Gusti Haqiqiansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
The purposes of this research is to analyze the financial feasibility of the amplang business Ud Ogi Passompe to see whether this business is feasible or not using investment criteria with NVP, IRR, Net B / C Ratio and Payback Period. This study used a field survey method, its sampling in the form of case studies. The results showed that from the financial aspect, amplang business is feasible to run and develop. as evidenced by the investment criteria, with an NVP value of IDR 1.683.306.559, IRR of 40%, Net BCR of 2.75 and a payback period of 2.91 years (34.9 months). Keywords : Feasibility Analysis, Amplang, Financial.